Macro-Structural Policies and Income Inequality in Low-Income Developing Countries - Fabrizio, Stefania (Staff Discussion Notes; Staff Discussion Notes ;, 2017)
Despite sustained economic growth and rapid poverty reductions, income inequality remains stubbornly high in many low-income developing countries. This pattern is a concern as high levels of inequality can impair the sustainability of growth and macroeconomic stability, thereby also limiting countries' ability to reach the Sustainable Development Goals. This underscores the importance of understanding how policies aimed at boosting economic growth affect income inequality. Using empirical and modeling techniques, the note confirms that macro-structural policies aimed at raising growth payoffs in low-income developing countries can have important distributional consequences, with the impact dependent on both the design of reforms and on country-specific economic characteristics. While there is no one-size-fits-all recipe, the note explores how governments can address adverse distributional consequences of reforms by designing reform packages to make pro-growth policies also more inclusive.